Design and Evaluation of a Personalized Cancer Treatment System using Human-Computer Interaction Techniques - Martínez Porras, Alexandra (2016)
This paper presents a case study where Human-Computer Interaction techniques were applied in the design and evaluation of a health system. The system consisted of a software platform that supports personalized cancer chemotherapy based on a tumor chemosensitivity assay. The essential background on personalized cancer treatment is provided. The system was designed using “contextual design,” a usercentered technique that involves contextual inquiry, interpretation, work modeling, consolidation, visioning, storyboarding and paper prototyping. The most salient products from the design phase and details of the system implementation are shown. The system was assessed using the Heuristic Evaluation method, which is a usability inspection performed by experts. Results from this evaluation indicate that only one of ten heuristics was missing from the system, while five were partially covered and four were fully covered.